Thermoelectric microstructures of Bi2Te3/Sb2Te3 for a self-calibrated micropyrometer - Gonçalves, L. M. (2005)
The fabrication (using planar thin-film technology) of Bi2Te3 and Sb2Te3 microstructures, with high thermoelectric figure of merit, suitable for incorporation in Peltier elements and thermopiles, is reported. The microstructures were fabricated by co-evaporation of Bi and Te, for the n-type element, and Sb and Te, for the p-type element, on a 25 µm-thick polyimide (kapton) substrate. Kapton film is a flexible, robust substrate with a low thermal conductivity. While the plastic mechanical properties allow conformal coverage of surfaces with many different shapes without apparent damage of film or substrate, Kapton low conductivity ensures that the devices will not be thermally shorted through the substrate. High figures of merit are reported, sufficient to achieve more than 10ºC of cooling over a 1 mm2 area.